Role of CTCF in the regulation of microRNA expression - Saito, Yoshimasa; Saito, Hidetsugu (Frontiers in Genetics, 2012)
MicroRNAs (miRNAs) are small non-coding RNAs that regulate expression of various target genes. MiRNAs are expressed in a tissue-specific manner and play important roles in cell proliferation, apoptosis, and differentiation. Epigenetic alterations such as DNA methylation and histone modification are essential for chromatin remodeling and regulation of gene expression including miRNAs. The CCCTC-binding factor, CTCF, is known to bind insulators and exhibits an enhancer-blocking and barrier function, and more recently, it also contributes to the three-dimensional organization of the genome. CTCF can also serve as a barrier against the spread of DNA methylation and histone repressive marks over promoter regions of tumor suppressor genes. Recent studies have shown that CTCF is also involved in the regulation of miRNAs such as miR-125b1, miR-375 and the miR-290 cluster in cancer cells and stem cells. MiR-125b1 is a candidate of tumor suppressor and is silenced in breast cancer cells. On the other hand, miR-375 may have oncogenic function and is overexpressed in breast cancer cells. CTCF is involved in the regulation of both miR-125b1 and miR-375, indicating that there are various patterns of CTCF-associated epigenetic regulation of miRNAs. CTCF may also play a key role in the pluripotency of cells through the regulation of miR-290 cluster. These observations suggest that CTCF-mediated regulation of miRNAs could be a novel approach for cancer therapy and regenerative medicine.